DISTRIBUSI Pb DAN Cu PADA BERBAGAI UKURAN PARTIKEL SEDIMEN DI PELABUHAN BENOA - E. Sahara (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2009)
This paper discusses the distribution of Pb and Cu in various particle sizes of sediment collected fromBenoa Bay, Bali. The particle sizes of sediment observed were >300; 300 – 100; 100 – 88,88 – 63 and <63 mm. Priorto the determination of both heavy metals, the sediments were digested with the mixture of HNO3 and H2O2 (1:1) at120oC. The measurements of the metal concentrations were performed by the use of Atomic AbsorptionSpectroscopy technique with the application of calibration method.It was found that the smaller the particle sizes the higher the metals concentraions were. The sediment of>300 mm contained Pb and Cu 0,74 – 0,77 mg/kg and 0,15 – 9,24 mg/kg, respectively. On the other hand, thesediment of < 63mm contained 21,36 – 53,01 mg/kg Pb and 104,14 – 132,82 mg/kg Cu. It was also observed thatthe distribution of particle sizes of all sediment collected from four sampling locations had similar patern.